2019
DOI: 10.1183/13993003.01929-2019
|View full text |Cite
|
Sign up to set email alerts
|

Roles of HIF1 and HIF2 in pulmonary hypertension: it all depends on the context

Abstract: @ERSpublications HIF1 and HIF2 can play complementary, opposing or unrelated roles in mediating the response to low oxygen levels in different cell types. This study shows HIF2 plays a dominant role in mediating the development of PH in response to environmental hypoxia. http://bit.ly/2Cy46sR Cite this article as: Waypa GB, Schumacker PT. Roles of HIF1 and HIF2 in pulmonary hypertension: it all depends on the context. Eur Respir J 2019; 54: 1901929 [https://doi.org/10.1183/13993003.01929-2019].Pulmonary hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…ERK activation can promote the proliferation of pulmonary artery fibroblasts, while Shufeiya recipe can downregulate the expression levels of Ras, p-MEK1/2, p-ERK1/2, and c-fos proteins in the ERK signaling pathway, thereby inhibitting PAECs fibrosis [ 5 ]. Activation of the HIF-1 signaling pathway in PAECs can promote the proliferation of pulmonary artery medial cells, and the expression of factors such as endothelin 1 [ 21 , 29 ]. The Toll-like receptor signaling pathway is closely related to the proliferation, apoptosis, migration, and interstitial transition of PAECs [ 22 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…ERK activation can promote the proliferation of pulmonary artery fibroblasts, while Shufeiya recipe can downregulate the expression levels of Ras, p-MEK1/2, p-ERK1/2, and c-fos proteins in the ERK signaling pathway, thereby inhibitting PAECs fibrosis [ 5 ]. Activation of the HIF-1 signaling pathway in PAECs can promote the proliferation of pulmonary artery medial cells, and the expression of factors such as endothelin 1 [ 21 , 29 ]. The Toll-like receptor signaling pathway is closely related to the proliferation, apoptosis, migration, and interstitial transition of PAECs [ 22 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…43 This HIF "switch" results in HIF-1 and HIF-2 playing divergent but complementary roles during the hypoxic response of tissues under pathophysiological conditions. 41,42,44 In our study, we used cell models to detect the effects of intermittent reoxygenation on HIF-1α and HIF-2α protein expression in HPASMCs. We found that intermittent short-duration reoxygenation disrupted the "switch" of HIF-1α and HIF-2α, which was probably one of the reasons why intermittent short-duration reoxygenation had a protective role in pulmonary arterial remodeling induced by hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1 drives the initial response to hypoxia, but during chronic hypoxic exposure it is HIF-2 that plays the major role in driving the hypoxic responses. 41,42 It's reported that when the HPASMCS is exposed to hypoxia, HIF-1α will rapidly accumulate and reach maximal levels from 2 to 6 hours of hypoxia. Afterwards, HIF-1a abundance was reduced and the HIF-2α reaches maximal levels at about 8 hours of hypoxia and remains elevated for more than 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, beneficial effects of HIF-2α inhibition on the development of PH were shown in different animal models [ 49 ]. Although HIF-1α plays an important role for HPV in pulmonary artery smooth muscle cells (PASMCs) and adventitial fibroblasts [ 110 ], endothelial HIF-2α appears to be the predominant factor in the pathogenesis of COPD-PH.…”
Section: Hif As a Key Molecular “Hub” In Lung Physiology And Copdmentioning
confidence: 99%